Meeting NCLB goals for highly qualified teachers: Estimates by state from survey data. - Blank, Rolf K.; Langesen, Doreen; Laird, Elizabeth; Toye, Carla; Bandeira de Mello, Victor (Education Policy Analysis Archives, 2004)
Abstract This article presents results of survey data showing teacher qualifications for their assignments that are comparable from state-to-state as well as data trends over time. The analysis is intended to help state leaders, educators, and others obtain a picture of highly qualified teachers in their state, and to be able to compare their state statistics with states across the nation. Since states have some flexibility in meeting the standard for highly qualified teachers outlined by NCLB, the analyses presented in this paper from a national survey may be useful as a common benchmark for use by states as they develop their own state-specific definitions and measures.